Pressure Induced Phase Transition and Superconducting Properties of PtH and IrH: A First Principles Study (Journal of Atomic and Molecular Sciences, 2014)
The electronic, structural, mechanical and superconducting properties ofPtH and IrH are investigated using first principles calculation based on density functionaltheory with generalized gradient approximation. The calculated lattice constantsat normal pressure are in good agreement with experimental and other theoreticalresults. Among the five crystallographic proposed structures investigated, thecubic phase is found to be more stable than the hexagonal ones. A new high pressureCsCl phase is predicted for Iridium hydride. The maximum superconducting transitiontemperature achieved in Platinum hydride and Iridium hydride are 23.8K and10K respectively. The calculated elastic constants indicate that both the hydrides aremechanically stable at ambient pressure.